2018
DOI: 10.1159/000490241
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare IT Utilization and Penetration among Physicians: Novel IT Solutions in Healthcare – Use and Acceptance in Hospitals

Abstract: Background: Healthcare IT (HIT) increasingly gains public attention and clinical daily relevance. A growing number of patients and physicians increasingly relies on IT services to monitor and support well-being and recovery both in their private and professional environment. This is assumed to develop rapidly in the upcoming years. Objective: This study examines the current status of HIT, its use and penetration among physicians in hospitals and researches utilization as well as future expectations regarding H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
(26 reference statements)
0
5
0
2
Order By: Relevance
“…Achieving this will require increased collaboration among physicians, MD manufacturers, and "IT stakeholders". [90][91][92][93][94] Two important medical aspects of mHealth prescribability were not addressed in the 165 included studies: the economic costs and benefits of mHealth innovations and the barriers to the prescription of mHealth applications. We shall now briefly discuss how these aspects have been approached in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Achieving this will require increased collaboration among physicians, MD manufacturers, and "IT stakeholders". [90][91][92][93][94] Two important medical aspects of mHealth prescribability were not addressed in the 165 included studies: the economic costs and benefits of mHealth innovations and the barriers to the prescription of mHealth applications. We shall now briefly discuss how these aspects have been approached in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Other limitations include the lack of information provided by health professionals about the different eHealth tools available and the discrepancy of eHealth use by physicians [19], thus resulting in the lack of promotion of these instruments. Finally, evidence-based medicine [20] and data security [21] are fundamental aspects; however, the utility and data security of the majority of eHealth tools have never been assessed.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was determined by considering the availability of subjects and the feasibility of enrolling physicians. A review of the existing literature [35][36][37][38] indicated a sample size of 200 to 400 physicians would be adequate to ensure data analysis and generalisability of responses.…”
Section: Study Populationmentioning
confidence: 99%